WAKAF AS A SHARIA ECONOMIC INSTRUMENT - An’im Fattach; Muhamad Imam Syairozi (Jurnal Scientia, 2023)
The majority of the population in Indonesia are Muslims, namely Islam. In Islam, not only worship is regulated, but activities such as muamalah are also regulated by Islam. One of the sharia economic institutions that plays an important role in the welfare of the people is waqf. Waqf has played its role in various aspects in financing various social, economic and cultural developments of society. And the most dominant in the fields of education and health. Many countries are funded by waqf in the construction of education and health facilities and infrastructure. The benefits of waqf are useful for supporting social and religious activities. There are various types of waqf, namely: cash waqf, stock waqf, sharia insurance policy waqf, land waqf, transportation waqf, water/well waqf. Thus Waqf is a source of funds from the community for the community. Thus making waqf an important instrument in the Islamic economy.